An integrated model of Brand Experience and Brand Loyalty: an examination of the mediation effects of customer satisfaction and brand trust - Noprianta, Dana Ananda; Mugiono, Mugiono; Yulianti, Ida (Profesional Muda Cendekia Publishing, 2024)
Growing consumer brand loyalty is necessary for businesses to survive and expand in the automotive industry, where fierce competition makes it harder for businesses to retain brand loyalty. The main objective of this study is to investigate how customer satisfaction and brand trust among Mitsubishi Motors customers mediate the effect of brand experience on brand loyalty. This study uses a quantitative methodology and falls under the explanatory research category. The population in the study was a customer of Mitsubishi Motors cars located in East Java Province. The data collection method uses a questionnaire distributed directly to 200 respondents at Mitsubishi Motors service dealers in East Java Province using convenience sampling techniques. The results from this research demonstrate that brand loyalty is significantly influenced by brand experience and brand trust. As a mediating factor, brand trust can close the gap between brand experience and brand loyalty. Nevertheless, the connections between brand experience and brand loyalty have yet to be significantly impacted by customer satisfaction. In order to cultivate client loyalty, Mitsubishi Motors must continue to uphold the trust that has been earned and raise customer satisfaction.